Different Reference Points: Tax Planning of Married Couples in East and West Germany - Katharina Erbe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This study evaluates the tax planning behavior of married couples with regard to the allocation of tax schedules between spouses in the context of the German income tax splitting. The focus lies on the disparities between East and West German couples. The assumption is that the tax planning behavior of married couples in Germany depends on different reference points referring to the theory by Tversky and Kahneman (1991). The analysis utilizes administrative data from statistics on German income tax returns for the year 2004 (FAST 2004). The result of an alternative specific conditional logit estimation indicates that West German couples are substantially more likely to choose different tax schedules than East Germans (between 17.6 and 19.1 percentage points). West Germans are more likely to allocate the advantageous tax bracket to the husband instead of the wife. Further logit and OLS estimations as well as a Blinder-Oaxaca decomposition support these findings. The conclusion of this analysis is that tax planning behavior of married couples is influenced by the differences in the socialization of people, caused by the fact that before 1990, East Germany had different tax institutions and political regimes compared to West Germany.
Keywords: H24; H31; H20; 330